PENGARUH PENDEKATAN BERMAIN TERHADAP AKTIVITAS GERAK SISWA DALAM MENGIKUTI MATA PELAJARAN PENDIDIKAN JASMANI (Studi pada Siswa Kelas VII SMP Negeri 3 Trienggadeng) - Muhammad Diah (Jurnal Sains Riset, 2019)
Physical education is basically an important part of the education system as a whole. Therefore the implementation of physical education must be directed at achieving that goal. In the process of learning physical education the teacher must be able to teach various basic skills, so that teachers are required to be more creative in providing physical education subjects. A teacher must be able to create something new or modify existing ones to be presented as attractive as possible so that students feel happy when attending physical education lessons. In carrying out the process of physical education learning, giving learning modifications through a play approach is one of the efforts that can be done. In the study studied the influence of the play approach on increasing student motion activity in class VII students of SMP Negeri 3 Trienggadeng. The purpose of this study were: (1) To find out whether through the play approach can improve students' movement activities in attending physical education learning in class VII SMP Negeri 3 Trienggadeng (2) To find out how much the increase in motion activity of students in participating in physical education learning through the approach of playing on class VII students of SMP Negeri 3 Trienggadeng. The type of research used in this study is quasi-experimental research using a quantitative approach. In this study there are two variables which consist of independent variables namely motion activity and the dependent variable namely the play approach. The research instrument used in the study used a pedometer. The population in this study were students of SMP Negeri 3 Trienggadeng, samples were taken using cluster random sampling techniques as many as 33 students of class VII. Data analysis using t-test for similar samples. Based on the results of the study, it can be seen the average value and standard deviation of the learning outcomes of the motion activity between the pre-test and post-test. The average learning outcomes of students' motion activities in the pre-test were 840.94 with a standard deviation of 58.778. Post-test obtained the average learning outcomes of student motion activities is 1456.67 with a standard deviation of 168.353. The mean value of the difference between the pre-test and post-test is 615,727 with a standard deviation of 182,971. Based on the results of statistical tests obtained a value of 0,000, it can be concluded that there is a significant difference between the pre-test and post-test amounting to 73.2%. So the play approach has a significant influence on increasing student motion activity in class VII students of SMP Negeri 3 Trienggadeng. Keywords: game approach, learning outcomes and physical activity